Comparative Analysis of Financial Risk Between Conventional and Shariah Banks: A Perspective of Market, Liquidity, and Credit Risks - Indri Iswardhani; Rahayu Alkam; Ade Ikhlas Amal Alam (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to compare financial risk management between conventional and Shariah banks in Indonesia. Financial risk is measured using three key indicators: Net Interest Margin (NIM) as a proxy for market risk, Current Ratio (CR) for liquidity risk, and Non-Performing Loan (NPL) for credit risk. The study employs the Mann–Whitney U Test to examine differences between the two types of banks using a sample of conventional and Shariah banks registered in Indonesia. The results indicate no significant differences between conventional and Shariah banks in terms of NIM and CR, although Shariah banks exhibit a higher yet more volatile NIM and a more stable CR. However, a significant difference is found in NPL, where Shariah banks display higher NPL ratios than conventional banks. These findings suggest that although both types of banks differ in their approaches to managing market and liquidity risks, Shariah banks are more vulnerable to credit risk, as reflected in their higher NPL levels. This study is expected to provide insights for banks and regulators to enhance risk management in both banking systems and serve as a foundation for developing more effective risk management policies in the conventional and Shariah banking sectors.